Germination and establishment of Teramnus labialis (L.f.) Spreng plants are affected by scarification treatment used - Yanier Acosta; Sershen; Jorge A. Sánchez; Inaudis Cejas; Dayamí Fontes; Marcos E. Martínez-Montero (Botan‪ical Sciences)
Background: Some of the species that make up the legume family are used as animal feed and to improve soil fertility. However, their use is limited due to low seed availability and low germination rates.